Psychometric Properties of a New Questionnaire Assessing the Mothers' Knowledge and Perception About the Oral Health of Their School Children - Zahra Momeni; Katayoun Sargeran; Reza Yazdani; Shirin Shahbazi Sighaldeh (Tehran University of Medical Sciences, 2022)
Objectives: The aim of the present study was to develop and evaluate the psychometric properties of an instrument in Persian to assess the mothers' knowledge, and perception about oral health of school children. Materials and Methods: A sequential exploratory mixed method design consisting of qualitative and quantitative phases was performed. We developed the questionnaire by inductive-deductive method, through a synthesis of literature review and a qualitative study with semi-structured interviews and focus group discussions. Face and content validity of the items were assessed by consulting a panel of 11 experts. In the quantitative phase, an exploratory factor analysis was performed using data from a cross-sectional study with a sample of 303 mothers. Reliability analysis with test-retest approach and Cronbach's alpha coefficient and intra-class correlation coefficient (ICC) was done. Results: Pre-final version of the scale consisted of 120 items extracted from the qualitative study and literature review. After content and face validity, 92 items were chosen with the greatest agreement between experts, with a content validity index (CVI) >0.8 and content validity ratio (CVR) of 0.59. The final questionnaire covered 62 items. The overall Cronbach's alpha was 0.94 and it ranged from 0.87 to 0.97 for the subscales. The ICC ranged from 0.91 to 0.98 (Cronbach's alpha ≥0.70). Conclusion: The present study introduced a valid and reliable questionnaire for assessment of the mothers' perception regarding school children's oral health. It can be used as a standardized measure for public health surveillance and evaluation of oral health promotion programs. Keywords: